2015
DOI: 10.1186/s12888-015-0546-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cortical thickness in right Heschl’s gyrus associated with auditory verbal hallucinations severity in first-episode schizophrenia

Abstract: BackgroundAuditory verbal hallucinations (AVHs) represent one of the most intriguing phenomena in schizophrenia, however, brain abnormalities underlying AVHs remain unclear. The present study examined the association between cortical thickness and AVHs in first-episode schizophrenia.MethodHigh-resolution MR images were obtained in 49 first-episode schizophrenia (FES) patients and 50 well-matched healthy controls (HCs). Among the FES patients, 18 suffered persistent AVHs (“auditory hallucination” AH group), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 44 publications
3
30
4
Order By: Relevance
“…Overall, findings were heterogeneous, with few direct replications. In schizophrenia, the most consistent findings were reductions in CT in the left or right temporal gyrus for patients with hallucinations compared to those without 75,76,94 , coincident with the reductions in GM in left MTG observed in the meta-analysis ( Figure 3). However, two studies reported increases in GM in temporal regions with hallucinations 88,90 .…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Overall, findings were heterogeneous, with few direct replications. In schizophrenia, the most consistent findings were reductions in CT in the left or right temporal gyrus for patients with hallucinations compared to those without 75,76,94 , coincident with the reductions in GM in left MTG observed in the meta-analysis ( Figure 3). However, two studies reported increases in GM in temporal regions with hallucinations 88,90 .…”
Section: Resultssupporting
confidence: 60%
“…28 studies employed a regional and/or non-voxelwise approach to evaluate structural MRI data with respect to hallucination status: seven studies performed VBM restricted to predefined ROIs 43,61,69-73 , one performed sourcebased morphometry 74 , nine explored cortical thickness (CT) and/or surface area [75][76][77][78][79][80][81][82][83] , three investigated gyral/sulcal properties 43,84,85 , and 11 assessed structure-specific shape parameters 43,81,83,[86][87][88][89][90][91][92][93] . Results are summarized in Tables 5-6.…”
Section: Resultsmentioning
confidence: 99%
“…The present finding of significant group differences between AH+ and AH− patients only in the left hemisphere is concordant with both Van Swam et al 30 who reported thinner cortex in the left HG in patients with AH compared to non-hallucinating patients, and Oertel-Knöchel et al 31 who found a negative correlation between predisposition towards hallucinations and cortical thickness in the left STG. Our findings differ from those of Chen et al 32 who reported significantly thinner cortex only in the right HG in patients with a lifetime history of AH compared to non-hallucinating first-episode schizophrenia patients. However, their supplementary data indicated that patients with AH also had reduced thickness in the left HG gyrus compared to non-hallucinating patients.…”
Section: Discussioncontrasting
confidence: 57%
“…Only a few previous studies have investigated if thickness of the auditory cortex is related to AH in schizophrenia patients, [30][31][32] and previous sample sizes have been small, ranging between 20-49 patients. The present finding of significant group differences between AH+ and AH− patients only in the left hemisphere is concordant with both Van Swam et al 30 who reported thinner cortex in the left HG in patients with AH compared to non-hallucinating patients, and Oertel-Knöchel et al 31 who found a negative correlation between predisposition towards hallucinations and cortical thickness in the left STG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation